A study of quality of life in people with mycosis fungoides and Sézary syndrome. (28th February 2020) - Molloy, K.; Jonak, C.; Sherida, F.J.; Woei‐A‐Ji, H.; Guenova, E.; Busschots, A.M.; Bervoets, A.; Hauben, E.; Knobler, R.; Porkert, S.; Fassnacht, C.; Cowan, R.; et al.
Summary: Mycosis fungoides (MF) is the commonest type of skin lymphoma and is part of a group of conditions known as cutaneous T‐cell lymphomas (CTCL). MF can appear as flat/raised, smooth/scaly red lesions known as patches and plaques, making it difficult to tell apart from eczema or psoriasis. Raised "lumps" called tumours can appear and the disease can become more serious. Sézary syndrome (SS) is a leukaemic form of CTCL and has an extensive red, itchy rash over most of the body, the presence of cancerous cells in the blood, and enlarged lymph glands. MF/SS can reduce patient quality of life (QoL) due to symptoms including itch and pain, poor self‐esteem secondary to cosmetic disfigurement, and can impair interpersonal relationships. In this article, we examine QoL in patients with MF/SS in a large international research study called PROCLIPI, using a questionnaire called Skindex‐29 which asks patients to comment on skin related questions which may affect their life enjoyment. We identified a number of important determinants of worse QoL in MF/SS including: female gender, patients diagnosed with SS and those with more widespread disease. Disease features which were associated with more impaired QoL included alopecia (hair loss) and confluent erythema (red patches and plaques merging together to form larger areas of affected skin). Combining all these factors together, we found that female patients, alopecia and confluent erythema were the most important. Given that females had worse QoL, we examined more closely which items in the Skindex‐29 questionnaire differed between males and females. Female patients experienced more burning, stinging, itch and irritation on their skin and greater feelings of depression, shame, embarrassment and annoyance with their diagnosis of MF/SS. Our research study has highlighted important aspects of QoL in MF/SS and emphasizes the urgent need for a more comprehensive QoL questionnaire to address not only the skin related aspects of the disease, but also the effects of cancer and its treatment on patient QoL. This is a summary of the study: Characteristics associated with significantly worse quality of life in mycosis fungoides/Sézary syndrome from the Prospective Cutaneous Lymphoma International Prognostic Index (PROCLIPI) study Abstract : Linked Article: Molloy et al. Br J Dermatol 2020; 182 :770–779